The Study of Religious Pluralism In The View of the Qur'an: Thematic Interpretation Approach - Zaenal Abidin (Jurnal Ar Ro'is Mandalika (Armada), 2021)
Pluralism is one study that is often of concern to various intellectual circles; Both Muslim scholars and orientalism. The various views that are "proclaimed" have different thinking foundations and are inseparable from the scientific capacity possessed. Studies of religious pluralism are based on several approaches such as philosophical, social and theological approaches as a basis for thinking so that it penetrates all aspects of today's society. The Quran as a reference that has a comprehensive nature is able to penetrate all lines of people's lives related to dogma and teachings contained therein. Almost all of its verses relate to standard rules both personal and group. The verses contained in it even more talk about social life that requires everyone to respect and respect each other between religious or interfaith people. Plurality is plurality based on virtue (uniqueness) and distinctiveness. Plurality cannot be included in a unity that has no parts that do not create its own "virtues", "uniqueness", and "distinctiveness". Without unity that covers all aspects, it is inconceivable that plurality, uniqueness, distinctiveness or plurality. For the sake of creating a plurality, all lines of society must dismiss double standards in the order of life which will later become a bridge so that it is in accordance with the ideology of all peace-loving religions.